RURAL DEVELOPMENT PROGRAMS IN ASSAM: AN ANALYSIS - Krishna Kamal Borah, M.A. M.Ed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Rural development is not only the development of the rural area but also the development of all-round development of the society. It means sustained growth of income of the rural people along with the distribution of income and economic assets in favor of the poorer sections of the community in such a way as to progressively remove unemployment and poverty. With the progressive removal of poverty, rural development also brings about an improvement in social, educational, economic, health, cultural aspects, and other aspects of rural life (Mitra, 1985). Rural development is the prior objective of development planning for every state in India. In Assam, most of the people live in rural areas of the state and most of them are found poverty ridden and economically backward. The state government has been giving special trust for the elimination of rural poverty as well as upliftment of the economic condition of people in rural areas. To achieve the objective, the state government has been implementing various poverty alleviation programs undertaken by the government of India. The Panchayat & Rural Development, Assam has been implementing various state and centrally sponsored programs through networks of 27 DRDAs, 21 Zila Parishads, 219 Community Development Block, 188 Anchalik Panchayat, and 2202 Gaon Panchayat. The programs that are under the sector of rural development are sponsored by both central and state governments. The present investigator wants to examine the different rural development schemes of the government sector and analyze various problems of rural development in Assam.